Tariqah al-Qawa'id wa at-Tarjamah wa Fa'aliyyatuha fi as-Sahah at-Ta'limiyyah - Adam Alhaji Tafida (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
This research aims to introduce the Arabic language situation in Jigawa state-Nigeria, also to disclosure the effectiveness of the grammar and translation method in the development of students language skills and to find a suitable method for the development of language skills. The researcher used the descriptive method to conduct this study, and the most important outcome of the study includes; The grammar and translation method is not appropriate to the objectives of the teaching Arabic language in Jigawa state. The content of the Arabic language in this state is above the students' mental capacity, and does not take into account the individual differences between the students. This study found that the Arabic language teacher in this state, is not aware of the objectives of teaching of Arabic language. There are problems facing students understanding of Arabic language courses, as a result of lack of use of appropriate teaching processes, such as lack of materials and the appropriate teaching aids, and resorting to translation more than explanation with acting, and drawing on the blackboard, and so on.